Implementasi Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Literasi Digital di SMA Al Muslim Sidoarjo - Rizkiyah, Alfiyatur; Masfufah, Masfufah; M, Amir Bandar Abdul (Lembaga Yasin AlSys, 2025)
The digital era has brought significant changes to various aspects of life, including the field of education. Information and communication technology has rapidly developed, influencing the way we acquire, process, and disseminate information. One relevant and important approach in this context is digital literacy-based learning. The integration of technology with Islamic religious education materials can have a substantial impact. For instance, in teaching Fiqih about the rituals of Hajj, teachers can utilize instructional videos that explain the sequence of manasik haji in detail or design simple interactive simulations to help students better understand the process. Meanwhile, for Aqidah and Akhlaq lessons, teachers can guide students to compose short sermons that encourage good behavior on social media, basing their arguments on relevant religious texts or verses. Students can then demonstrate their understanding by uploading these sermons to social media platforms. This study employs qualitative research methods. The data sources include direct observations at SMA Al Muslim Sidoarjo and interviews with key informants such as the principal, Islamic education teachers, and students. The data collection techniques used are interviews, observations, and documentation. The research findings indicate that: 1) The implementation of digital literacy in Islamic education learning involves several stages. The first is the planning stage, where teaching modules are prepared in line with the learning objectives. The second stage is the execution, which involves using the school's digital application (My-Al Muslim) to easily access necessary learning resources. The third stage is the evaluation process, where students are assigned tasks. 2) Supporting factors include the provision of facilities such as computers, LCD projectors, and WiFi. On the other hand, the inhibiting factor is the unstable internet connection.